THE EFFECT OF EMOTIONAL INTELLIGENCE ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN GHANA: THE MEDIATION ROLE OF RELATIONSHIP MARKETING, SERVICE QUALITY, CUSTOMER SATISFACTION - Danquah, Emelia (British Journal of Marketing Studies, 2015)
This study examines the effect of emotional intelligence on financial performance of commercial banks in Ghana from the perspective of the mediation role of relationship marketing, service quality and customer satisfaction. It goes further to indicate the relative impacts of these mediating variables on financial performance. A complete picture of the monetary effects of investing in the enhancement of employees’ emotional intelligence is hence the core of this paper. The study is a descriptive quantitative study in which a sample of 220 each of service providers and customers in 20 commercial banks in Ghana are used. Pearson’s correlation test, partial correlation test and ordinary least squares regression analysis were used to analyse data. According to findings, emotional intelligence positively relates to relationship marketing (r = .804, p = .000), service quality (r = .601, p = .000), customer satisfaction (r = .426, p = .000) and financial performance (r = .734, p = .000). Emotional intelligence also significantly predicts relationship marketing, service quality, customer satisfaction and financial performance by contributing 64.7%, 63.2%, 23.2% and 32% of the variance respectively. It is made evident that relationship marketing provides the most dominant mediation in the relationship between emotional intelligence and financial performance in the face of service quality and customer satisfaction. Commercial banks are therefore encouraged to deploy resources towards equipping their service providers with emotional intelligence